Methods for Cultivating Character Education at the Al-Huda Modern Islamic Tahfizh Boarding School Cawan - Jamal Thoriq; Meti Fatimah (South Sulawesi Education Development (SSED), 2025)
The aim of this research is to find out in depth what methods are used by the principal and teacher staff in instilling character education for students at Modern Islamic Tahfizh Boarding School (PTPM) Al-Huda Cawan Klaten. It turns out that character education has not been successfully applied to all students. Certain methods are needed so that students have noble character and obey the rules. To achieve the objectives of this research, a descriptive qualitative approach was used involving the principal, teachers and students as the main sources of information. Data collection was carried out by conducting observations, interviews and documentation as well as relevant literature results. Data analysis uses interactive analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The research results show that, firstly, Islamic boarding schools are an effective educational institution that does not only focus on teaching religious knowledge, but also on developing the character and morals of students. The program designed and implemented consistently by the Islamic boarding school has proven to be a support for the formation of a better generation with good character and noble morals. Second, the method of instilling character education for PTPM Al-Huda Cawan Klaten students includes giving advice/motivation, example/uswah, habituation, ta'lim/learning and strengthening. This research does not discuss methods of instilling certain character education, for example being religious, independent, hard work, creative, tolerant, honest and so on in PTPM Al-Huda Cawan Klaten students.